Microwave irradiation-induced deterioration of rock mechanical properties and implications for mechanized hard rock excavation - Zheng Yang; Ming Tao; Muhammad Burhan Memon; Dengdeng Zhuang; Yan Zhao (Journal of Rock Mechanics and Geotechnical Engineering)
In this study, a novel microwave-water cooling-assisted mechanical rock breakage method was proposed to address the issues of severe tool wear at elevated temperatures, poor rock microwave absorption, and excessive microwave energy consumption. The investigation object was sandstone, which was irradiated at 4 kW microwave power for 60 s, 180 s, 300 s, and 420 s, followed by air and water cooling. Subsequently, uniaxial compression, Brazilian tension, and fracture tests were conducted. The evolution of damage in sandstone was measured using active and passive nondestructive acoustic detection methods. The roughness of the fracture surfaces of the specimens was quantified using the box-counting method. The damage mechanisms of microwave heating and water cooling on sandstone were discussed from both macroscopic and microscopic perspectives. The experimental results demonstrated that as the duration of the microwave irradiation increased, the P-wave velocity, uniaxial compressive strength (UCS), elastic modulus (E), tensile strength, and fracture toughness of sandstone exhibited various degrees of weakness and were further weakened by water cooling. Furthermore, an increase in the microwave irradiation duration enhanced the damaging effect of water cooling. The P-wave velocity of the sandstone was proportional to the mechanical parameters. Microwave heating and water cooling weakened the brittleness of the sandstone to a certain extent. The fractal dimension of the fracture surface was correlated with the duration of microwave heating, and the water-cooling treatment resulted in a rougher fracture surface. An analysis of the instantaneous cutting rate revealed that water cooling can substantially enhance the efficiency of microwave-assisted rock breakage.